Pancreatic mitochondrial complex I exhibits aberrant hyperactivity in diabetes() - Wu, Jinzi (Biochem Biophys Rep, 2017)
It is well established that NADH/NAD(+) redox balance is heavily perturbed in diabetes, and the NADH/NAD(+) redox imbalance is a major source of oxidative stress in diabetic tissues. In mitochondria, complex I is the only site for NADH oxidation and NAD(+) regeneration and is also a major site for production of mitochondrial reactive oxygen species (ROS). Yet how complex I responds to the NADH/NAD(+) redox imbalance and any potential consequences of such response in diabetic pancreas have not been investigated. We report here that pancreatic mitochondrial complex I showed aberrant hyperactivity in either type 1 or type 2 diabetes. Further studies focusing on streptozotocin (STZ)-induced diabetes indicate that complex I hyperactivity could be attenuated by metformin. Moreover, complex I hyperactivity was accompanied by increased activities of complexes II to IV, but not complex V, suggesting that overflow of NADH via complex I in diabetes could be diverted to ROS production. Indeed in diabetic pancreas, ROS production and oxidative stress increased and mitochondrial ATP production decreased, which can be attributed to impaired pancreatic mitochondrial membrane potential that is responsible for increased cell death. Additionally, cellular defense systems such as glucose 6-phosphate dehydrogenase, sirtuin 3, and NQO1 were found to be compromised in diabetic pancreas. Our findings point to the direction that complex I aberrant hyperactivity in pancreas could be a major source of oxidative stress and β cell failure in diabetes. Therefore, inhibiting pancreatic complex I hyperactivity and attenuating its ROS production by various means in diabetes might serve as a promising approach for anti-diabetic therapies.